GIRLS, PERFORMANCE AND ACTIVISM demanding to be heard. - Edell, Dana. ([S.l.] : ROUTLEDGE, 2021)
Girls, Performance, and Activism offers artists, activists, educators, and scholars a comprehensive analysis, celebration, and critique of the ways in which teenage girls create and perform activist theater. Girls, particularly Black and Latinx teenagers, are using the tools of performance to share their stories, devise new ones, and use the stage to advocate for social change. Interweaving interviews, poetic text, drama, and theory, this book provides readers with a comprehensive understanding of how and why this field erupted and the ways in which girls are using performance to transform themselves and enact change in their communities. As a white woman who has collaboratively created theater with hundreds of girls of color over the past20 years, Dana Edell offers strategies for engaging with girls across difference through an intersectional lens in order to acknowledge the ways in whichrace, gender, age, class, ability, and sexuality influence girls' experiences and relationships with adult collaborators as they work to create meaningful, impactful, and often personal activist performances. This is the go-to handbook for teachers, theater directors, and performance makers who want to create politically engaged work with teenage girls.
Keywords: Teenage girls -- Political activity; Teenage girls, Black -- Political activity; Theater -- Political aspects; Feminist theater; PERFORMING ARTS / General; POLITICAL SCIENCE / Political Freedom & Security / Human Rights